Green and socioeconomic infrastructures in the Brazilian Amazon: implications for a changing climate. (7th February 2019) - da Silva, José Maria Cardoso; Prasad, Shivangi
Abstract : Amazonia is one of the world's most vulnerable regions to climate change but few studies pinpointing priority areas for local adaptation programmes exist. This paper aims to identify socio-climatic hotspots among the 515 municipalities that compose the Brazilian Amazon by using a three-step process. First, we identified the regional social hotspots, that is, municipalities that have currently low adaptive capacity, by calculating a composite infrastructure index based on the assessment of both current green and socioeconomic infrastructures. Second, we used a Regional Climate Change Index to identify the climate change hotspots, that is, those municipalities that have a high likelihood to experience future climate change risks. Third, we evaluated the geographic coincidence of social and climate change hotspots to identify the socio-climatic hotspots. We found that 117 municipalities are regional social hotspots and that 60 municipalities are regional climate change hotspots. Forty-six municipalities are considered as socio-climatic hotspots because they have very low to low composite infrastructure indices and very high climate risk indices. Local institutional capacity to integrate and execute national-level policies that enhance local adaptive capacity is a major constraint across the region. To face the challenges associated with climate change, municipalities in the Brazilian Amazon should embrace a more sustainable development model. Sustainable development, in the context of the Brazilian Amazon, implies conservation of the existing green infrastructure through the expansion of protected areas and indigenous lands, restoration of green infrastructure in areas of deficit, and substantial investments in urban socioeconomic infrastructures to foster a knowledge-based economy. Although local sustainable development and adaptation plans are essential across the entire region, the 46 municipalities identified in this study as regional socio-climatic hotspots could be prioritized for action.